A Late Bronze Age foreign elite? Investigating mobility patterns at Seddin, Germany - Anja B. Frank; Jens May; Serena Sabatini; Franz Schopper; Robert Frei; Flemming Kaul; Susanne Storch; Svend Hansen; Kristian Kristiansen; Karin M. Frei (PLoS ONE, 2025)
During the Late Bronze Age (ca. 11th-8th century BCE), far-reaching and extensive trade and exchange networks linked communities across Europe. The area around Seddin in north-western Brandenburg, Germany, has long been considered as at the core of one such networks. The degree of which the exchange practices involved in the circulations of goods and ideas was facilitated by people of different origins settling along the networks remains to be understood. To address this question, this study presents Sr isotope data of 29 cremated petrous bones from five neighbouring Late Bronze Age burial sites around Seddin, including the 9th century BCE Wickbold I burial mound. Modern environmental samples and archaeological soil samples were also analysed for 87Sr/86Sr to establish a bioavailable reference baseline for the region. The results suggest that modern water and archaeological soil samples appear to be best suited proxies for defining a 87Sr/86Sr baseline that can reliably be used to trace Bronze Age mobility at Seddin, while the modern soil and plant sample 87Sr/86Sr data seem to reflect changes inherent to natural carbonate leaching of the glaciogenic surface sediments over time and/or recent anthropogenic contamination, such as fertilizers, rendering their use as representative archives for bioavailable Sr in the study of past human mobility, at least in the greater Seddin region, problematic. The comparison of the petrous bone 87Sr/86Sr signatures to the proposed water Sr isotope baseline reveals an overwhelming presence of non-locals in the investigated grave sites, with only two of 22 individuals falling within the local baseline. This study suggests complex mobility patterns of the elite community around Seddin during the Late Bronze Age.